2013
DOI: 10.1016/j.febslet.2013.10.028
|View full text |Cite
|
Sign up to set email alerts
|

ESET histone methyltransferase regulates osteoblastic differentiation of mesenchymal stem cells during postnatal bone development

Abstract: To investigate the effects of histone methyltransferase ESET (also known as SETDB1) on bone metabolism, we analyzed osteoblasts and osteoclasts in ESET knockout animals, and performed osteogenesis assays using ESET-null mesenchymal stem cells. We found that ESET deletion severely impairs osteoblast differentiation but has no effect on osteoclastogenesis, that co-transfection of ESET represses Runx2-mediated luciferase reporter while siRNA knockdown of ESET activates the luciferase reporter in mesenchymal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…found that mesenchymal deletion of SETDB1 led to long bone defects and significant decrease in trabecular bone in both embryos and postnatal mice. 32,33 These mice also exhibited decreased osteoblasts in long bones, but normal osteoclast formation. These data indicate that SETDB1 is required for differentiation of MSCs into osteoblasts.…”
Section: Set Domain-containing Histone Methyltransferasesmentioning
confidence: 94%
See 1 more Smart Citation
“…found that mesenchymal deletion of SETDB1 led to long bone defects and significant decrease in trabecular bone in both embryos and postnatal mice. 32,33 These mice also exhibited decreased osteoblasts in long bones, but normal osteoclast formation. These data indicate that SETDB1 is required for differentiation of MSCs into osteoblasts.…”
Section: Set Domain-containing Histone Methyltransferasesmentioning
confidence: 94%
“…Consistent with these results, knockdown of SETDB1also enhances RUNX2-mediated gene transcription in vitro , which may be caused by the decrease of H3K9me3 in the promoters of RUNX2 target genes. 33 Although RUNX2 is necessary for osteoblast differentiation, when transgenically over-expressed, it can inhibit osteoblast maturation. 34 Collectively, SETDB1 inhibits osteogenic differentiation of MSCs, but it is required for normal skeletal formation due to its ability to repress hyperactive RUNX2-mediated transcription.…”
Section: Set Domain-containing Histone Methyltransferasesmentioning
confidence: 99%
“…H3K9 dimethylation and trimethylation are both repressive histone modifications and are mainly catalyzed by G9a/GLP and SUV39H1/2, respectively, mediating the formation of heterochromatic regions through interaction with HP1 [61,62]. Knockdown of ESET or SETDB1, a H3K9 methyltransferase, causes bone defects in mice [63]. Mechanistically, the impairment of osteogenic differentiation results from histone methylationinduced aberrant expression of Runx2.…”
Section: H3k9 Methylationmentioning
confidence: 99%
“…Research on AT-rich interactive domain 5b (Arid5b), a transcriptional coregulator of Sox9, has shown that this molecule promotes chondrogenic differentiation by recruiting the H3K9 demethylase PHF2 to the promoters of the Sox9 target genes Col2a1 and Aggrecan, thereby decreasing H3K9me2 levels in these regions [63]. Moreover, another HDM, KDM4B, removes H3K9me3 marks on the promoter region of Sox9 and thus upregulates SOX9 expression [73].…”
Section: H3k9 Methylationmentioning
confidence: 99%
“…The methyltransferase SETDB1 (Set domain, bifurcated 1), also known as ESET, suppresses gene expression and modulates heterochromatin formation through H3K9me2/3 (Schultz et al 2002). Previous studies demonstrated that SETDB1 plays essential roles in the maintenance of embryonic stem (ES) cells (Bilodeau et al 2009, Yuan et al 2009, Lohmann et al 2010, articular cartilage and survival of neurons (Tan et al 2012, Lawson et al 2013. As conventional knockout of the Setdb1 resulted in mouse embryonic lethality (Dodge et al 2004), the roles of SETDB1 for spermatogenesis have not been examined extensively.…”
Section: Introductionmentioning
confidence: 99%